Training and testing of character - Harrington, Amy Myrtle (My University, 1891)
Introduction: As the progress of the human race advances, the great need of mankind is a firm and proper foundation on which to build up human characters. This is necessary to all who would make the most of their capabilities for usefulness and happiness. The foundation of every character is laid in the training and testing which it receives; and the nature of the resulting life will depend on the nature of the elements entering into it. Life is largely what education makes it; but only a comparatively small portion of the education of the world is obtained from books. It is chiefly the result of associations. If early associations be in the right channel, guiding to timely habits and quick and symmetrical movements in study, work, or play, the life that grows amid such influences will develop a force capable of removing the greatest difficulties, and an energy enduring for all time. It is these early influences and associations that lay the foundation of character in opinions and convictions upon which the whole structure depends. But the most important school for the training of character is the home. Here the mind of the child yielding readily to home influences, grows and develops either a strong, healthful character, or one utterly useless, according as the surroundings have been for good or for evil.
Citation: Harrington, Amy Myrtle. Training and testing of character. Senior thesis, Kansas State Agricultural College, 1891.
Morse Department of Special Collections
Keywords: Nurture; Home Life; Character; Child development; Theses; Manuscripts (documents)